Perkembangan Kognitif Mahasiswa pada Masa Dewasa Awal - Nur, Ridha Raudah; Latipah, Eva; Izzah, Ismatul (ARZUSIN, 2023)
The purpose of writing this article is to analyze the cognitive development of students in early adulthood. This type of research is literature study. Qualitative research is inductive using a flexible research design, data collection techniques in the form of documentation, data validity testing using triangulai, and data analysis techniques using content analysis. The results of this study indicate that there are many changes in the cognitive development of students in early adulthood, due to experiences that are supported by the cerebral cortex, especially the forebrain. Cognitive progress and brain growth of students in early adulthood are most fundamentally triggered by various major events experienced by students in life and while studying in college, which initially students' way of thinking is based on Piaget's theory, namely formal operational and experiencing a shift to post-formal which is relative and reflective. Perry is multi-minded, more relative thinking, and full relativism. Gisela is pragmatic thinking and cognitive complexity. Schaie phase achieves achievement and responsibility.